Avaliação do processo de restauração de um fragmento de mata ciliar na região de Santa Maria - RS - Amaral, Gilneia Mello do (2017)
Riparian forest is the vegetation adjacent to a body of water, which expands from slopes for large extensions. It is imperative that these areas are preserved and in many cases, is necessary its recovery. To evaluate the efficiency of recovery techniques and to verify if restoration is occurring is necessary to monitor these areas. In this context, the aim of this study is to evaluate the recovery evolution of a fragment of riparian forest in Santa Lagoão do Ouro, Santa Maria – RS. The study was conducted in 4 areas with 300 m2 each, divided in 4 plots per treatment. The treatments tested were: area in recovery process (AR), where was implanted a nucleation technique through planting native species in 2009; naturally regeneration process area (ARN), isolated since 2009 to evaluate natural revegetation; area with Pinus sp (AP); and area with native vegetation (MN). Emphasizing that the techniques used in AR and ARN are part of a study implanted in 2009 by Ceconi (2010), this work is part of the continuity of evaluation of the restoration process. To evaluate plants introduced in AR in 2009 was measured height (m), neck diameter (cm), diameter at chest height (DAP), crown diameter and death percentage of species. Species that presented a fast growth and large crown diameter were classified as group of Fill, the others as group of Diversity. Also, in the treatments AR and ARN was performed an evaluation of coverage by grasses, number of regenerating individuals and Shannon index (H’). It was evaluated in all treatments the composition of field residues, soil quality and enzyme activity of urease, β-glucosidase, acid phosphatase and hydrolysis of diacetate of fluorescein (FDA). The results were submitted to variance analysis at the level of 5% of error. The species planted on AR classified as Fill presented a height, neck diameter, DAP and crown diameter higher than the species of the Diversity group, being them: Ateleia glazioveana, Schinus terebinthifolius, Enterolobium contortisiliquum, Pelthophorum dubium, Casearia sylvestris, Luehea divaricata and Parapiptadenia rígida. The mortality rate in AR was 49,47%, being extinguished 5 species: Apuleia leiocarpa, Cabralea canjerana, Cedrela fissilis, Cupania vernalis and Diospyrus inconstans. The treatment ARN presented a higher percentage of grasses when compared with AR. The natural regeneration in AR was influenced by native species planted, while ARN presented higher amounts of invasive species. The Shannon index showed a higher diversity of species in AR when compared with ARN. The species planted in AR and classified as species of fill presented a higher height, higher neck diameter, higher diameter at chest height and higher crown diameter in comparison with the species located in the diversity group, however the mortality was lower. The treatment AP presented higher amounts of field residues, which was influenced by the large amount of needles, being in sequence the treatments AR, MN and ARN. In relation with the soil chemical analysis, organic matter increased in both areas with recovery process when compared with the levels of 2009. The value of OM in AR was close to MN and did not differ statistically. The ARN presented a lower value of OM, but still superior then AP. Thus, even though the plants used in AR have been growing slowly and with a high mortality rate until this moment, the nucleation technique used in AR is more adequate to recovery the area than the isolation process used in ARN. It occurred because of the low regeneration potential of the natural riparian forest and also the competition with grasses. From the species used in nucleation, is recommended in similar situations in the area the use of species classified as Fill, mainly due to its fast growth and ability of survive and establishment. The activity of FDA was higher at AR, being superior of MN, which did not presented statistical differences in comparison with ARN. Also, AP presented the lowest activity of FDA. The β-glucosidase values were different in all treatments tested, where MN presented the higher activity, followed by AR, ARN and AP. The phosphatase was statistically higher in MN, while in AR and ARN it was not found differences and AP presented a lower value. The urease did not presented statistical differences among treatments. Thus, the analysis of hydrolysis of diacetate of fluorescein, β-glucosidase and phosphatase were efficient to characterize the soil activity in areas with restoration process.